Motive und Ziele der Frauen bei der Partnerwahl (anhand deutschsprachiger Bekanntschaftsanzeigen und Profile auf den Webseiten) - Pasyk, Lyudmyla Adamivna; Пасик, Людмила Адамівна (ROSTranse Trade FZC company, 2017)
The article deals with the notions “motive” and “motivation” as well as with the means of expression of the motives and the aims by the women in the situation of partner choice. The material of the study is taken from the german electronic advertisements of acquaintance and Internet-questionnaries. The situation of partner choice is modeled in the form of actional frame. The slots of macro-propositional frame of the situation of partner choice (subject of choice, process of choice, object of choice, reason and purposes) are filled with different language units. The questionnaires give the expanded information about the addresser, her motives and aims, while the advertisements of acquaintance are limited to a smaller amount and contain mainly short, the most relevant (to the author’s mind) information. The motivs and the aims can differ. It depends on the situation and also on the personal desires of the women, who look for a partner. Due to the age of the women three groups were determined and the means of expression of main aims were specified.
Keywords: partner choice; motive; motivation; aim; woman